The application of the digital era and its effects on the granting of credits to natural persons in the municipal savings and credit banks of Peru - Pacheco Vizcarra, Milagros Yesenia (2023)
The objective of this investigation has been to determine how the use of the digital age favorably impacts the placement of personal loans in the municipal savings and credit banks of the country, period 2021 -2022, the type of investigation has been used is applied, for which we have worked with 96 workers from the 11 Municipal Savings and Credit Banks of Peru that make up the financial system, where it has been possible to determine that the digital age is an important component in the development of any type of financial entity such as This is the case of the Municipal Savings Banks because it has been possible to show through our results that 70% use social networks to become aware of the granting of networks, while 20% use the mobile application, it is recommended that financial entities take into account the digital era, for which work must be done on digital marketing, mobile applications and data validation processes for the or granting of credits considering that a good investment can bring great benefits of profitability.